1989
DOI: 10.1128/mcb.9.5.2181
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of mRNA cap-binding protein from Drosophila melanogaster embryos.

Abstract: A protein with specific affinity for the mRNA cap structure was purified both from the postribosomal supernatant and from the ribosomal high-salt wash of Drosophila melanogaster embryos by m7GTP-Sepharose However, in a cell-free system from Drosophila embryos, mRNA translation was specifically inhibited by these antibodies. The requirement of 35-kDa CBP for mRNA translation in Drosophila was diminished under ionic conditions in which the importance of mRNA cap structure recognition was reduced. Despite the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 47 publications
3
43
1
Order By: Relevance
“…We cloned sickle, hid and grim 5 0 UTRs into the monocistronic vector containing Firefly luciferase as a reporter (FLuc; Figure 2a) and assayed their translation competence in a cell-free Drosophila-embryo translation system. 16,17 As expected, the uncapped FLuc control mRNA was not translated efficiently in the extracts, whereas the uncapped reporters containing the 5 0 UTR of hid, grim and sickle conferred translation to the reporter at levels equivalent to the m 7 GpppG-capped FLuc control vector (cap-FLuc; Figure 2b). The same was observed for the cap-independent rpr and hsp70 mRNAs, which were used as controls in this experiment.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We cloned sickle, hid and grim 5 0 UTRs into the monocistronic vector containing Firefly luciferase as a reporter (FLuc; Figure 2a) and assayed their translation competence in a cell-free Drosophila-embryo translation system. 16,17 As expected, the uncapped FLuc control mRNA was not translated efficiently in the extracts, whereas the uncapped reporters containing the 5 0 UTR of hid, grim and sickle conferred translation to the reporter at levels equivalent to the m 7 GpppG-capped FLuc control vector (cap-FLuc; Figure 2b). The same was observed for the cap-independent rpr and hsp70 mRNAs, which were used as controls in this experiment.…”
Section: Resultsmentioning
confidence: 95%
“…Translation extracts were prepared from 0 to 12 h-old Drosophila embryos as described 16,17 for the indicated times at 251C. Translation extracts from heat-shocked embryos were prepared from pools of 0-12 h-old embryos that have been treated for 45 min at 371C and processed without further recovery.…”
Section: Methodsmentioning
confidence: 99%
“…This is true for Drosophila embryos [ 161 and wheat germ (Ravel, J.M., personal communication) systems. We found that eIF-2 -PL has no effect on translation of endogenous mRNAs of Drosophila embryo lysates (table 2) when this system is active in initiation because it is strongly inhibited by cap analogues [13] or pactamycin (table 2). Moreover, the translation of globin mRNA in a wheat germ system was also unaffected by the addition of concentrations of eIF-2 -PL that are active in reticulocyte lysates (table 2).…”
mentioning
confidence: 94%
“…The preparation of the cell-free extract from mouse liver has been described [12]. Drosophila embryo lysates [13] were the gift of F. Maroto of this laboratory.…”
Section: Preparationsmentioning
confidence: 99%
See 1 more Smart Citation